AGN-driven quenching of satellite galaxies. Issue 4 (28th June 2019) - Dashyan, Gohar; Choi, Ena; Somerville, Rachel S; Naab, Thorsten; Quirk, Amanda C N; Hirschmann, Michaela; Ostriker, Jeremiah P
ABSTRACT: We explore the effect of active galactic nucleus (AGN) feedback from central galaxies on their satellites by comparing two sets of cosmological zoom-in runs of 27 haloes with masses ranging from 10 12 to 10 13.4 $\rm {M}_{\odot}$ at z  = 0, with (wAGN) and without (noAGN) AGN feedback. Both simulations include stellar feedback from multiple processes, including powerful winds from supernovae, stellar winds from young massive stars, AGB stars, radiative heating within Strömgren spheres and photoelectric heating. Our wAGN model is identical to the noAGN model except that it also includes a model for black hole seeding and accretion, as well as AGN feedback via high-velocity broad absorption line winds and Compton/photoionization heating. We show that the inclusion of AGN feedback from the central galaxy significantly affects the star formation history and the gas content of the satellite galaxies. AGN feedback starts to affect the gas content and the star formation of the satellites as early as z  = 2. The mean gas-rich fraction of satellites at z  = 0 decreases from 15 per cent in the noAGN simulation to 5 per cent in the wAGN simulation. The difference between the two sets extends as far out as five times the virial radius of the central galaxy at z  = 1. We investigate the quenching mechanism by studying the physical conditions in the surroundings of pairs of satellites matched across the wAGN and noAGN simulations and find an increase in the temperature and relative velocity of the intergalactic gas.